An ultrastructural, biochemical and viscoelastic investigation into the hypercoagulable state of breast cancer patients and the implications for the disease - Bester, Megan J. (University of Pretoria, 2026)
Dissertation (MsC (Human Physiology))--University of Pretoria, 2019.